A new marine nematode genus Pseudoplatycoma with a new species from the Sulu Sea and revision of the subfamily Platycominae (Enoplida: Leptosomatidae) - Chen, Cheng-Ann (Zootaxa, 2015)
The nematode Pseudoplatycoma malaysianis n. gen. n. sp. is described from the Sulu Sea (Malaysia). The new genus is classified in the subfamily Platycominae Platonova 1976. Revision of the new genus and four other genera in Platycominae, resulted in four species from the genus Platycomopsis being transferred to other genera: P. dimorphica and P. mazjatzavi to the genus Platycoma; P. effilata to the genus Micoletzkyia; and P. gibbonensis to the genus Anticoma. Pilosinema is regarded as a asynonym of Platycomopsis and Platycomopsis paracobbi is regarded as a synonym for P. cobbi. A key for identification of the genera and species of Platycominae is presented.